2011
DOI: 10.1007/s00125-011-2287-1
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency as a risk factor for cystic fibrosis-related diabetes in the Scandinavian Cystic Fibrosis Nutritional Study

Abstract: Aims/hypothesis Many cystic fibrosis patients are vitamin D-insufficient. Cystic fibrosis-related diabetes is a major complication of cystic fibrosis. The literature suggests that vitamin D might possess certain glucose-lowering properties. We aimed to assess the relationship between vitamin D and cystic fibrosis-related glucose intolerance. Methods We enrolled 898 cystic fibrosis patients from Sweden, Norway and Denmark. Vitamin D intake was assessed using a seven-day food record. Serum 25-hydroxyvitamin D (s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
2
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 44 publications
0
20
2
2
Order By: Relevance
“…The correlation between vitamin D and Pearson's correlation coefficient r2 was -0.05, and 95% confidence interval (-1.556-69.522), with a p value of 0.667, denies the existence of a correlation between the two compared variables. We did not find any relation between the level of the vitamin D and the glycemia values in cystic fibrosis patients, although some studies suggest the effect of the vitamin D deficiency in diabetes occurrence and impaired glucose tolerance [23].…”
Section: -Hydroxyvitamin D and Glycaemiacontrasting
confidence: 85%
“…The correlation between vitamin D and Pearson's correlation coefficient r2 was -0.05, and 95% confidence interval (-1.556-69.522), with a p value of 0.667, denies the existence of a correlation between the two compared variables. We did not find any relation between the level of the vitamin D and the glycemia values in cystic fibrosis patients, although some studies suggest the effect of the vitamin D deficiency in diabetes occurrence and impaired glucose tolerance [23].…”
Section: -Hydroxyvitamin D and Glycaemiacontrasting
confidence: 85%
“…These vitamin D-related effects are relevant to CF because vitamin D deficiency is very common in these individuals (10). Adequate vitamin D status in CF, as determined by blood 25-hydroxyvitamin D [25(OH)D] concentrations, correlates with improved lung function (11,12), reduced pulmonary exacerbations (12) and hospitalizations (13), improved glucose tolerance (14), reduced inflammation (15) and decreased lung bacterial colonization (16). In a pilot clinical trial, we showed that high-dose vitamin D 3 , given to hospitalized CF patients during an acute pulmonary exacerbation, reduced inflammation and improved one-year survival (4,5); however, the impact of underlying vitamin D status and high-dose vitamin D administration on systemic metabolism in CF remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…For example, vitamin D is likely to improve respiratory function through its role in antimicrobial peptide and cytokine production and its association with muscle strength [40,41,43,44]. It is also associated with CFRD through potential involvement in islet function regulation, insulin production and secretion, and insulin sensitivity [42,46]. Its role in bone health and immune response has also implied an importance in pain management in CF [45].…”
Section: Fat-soluble Vitaminsmentioning
confidence: 97%